Gospel opportunity or gospel threat? : the church's debate on sexuality - Temple, Gray, 1941- (New York : Church Publishing, 1998)
Papers presented at conferences established by the Virginia Diocesan Center as a memorial to the Right Reverend Robert F. Gibson, Jr.
Includes bibliographical references.
Keywords: Homosexuality -- Religious aspects -- Episcopal Church -- Congresses; Ordination of gays -- Religious aspects -- Episcopal Church -- Congresses; Same-sex marriage -- Religious aspects -- Episcopal Church -- Congresses; Episcopal Church -- Doctrines -- Congresses